The ethnomedicinal plants of Purko, Maasai in Central Narok, Kenya - Hedges, Kristin; Evans, Timothy; Ole Kipila, Joseph (Ethnobotany Research and Applications, 2026)
Background: Indigenous plants are integral to the Maasai community’s healthcare throughout East Africa. This research documented traditional medicinal knowledge (TMK) among the Purko Maasai community in Kenya. While this knowledge has typically been orally transmitted, a request was made by local elders to write it down for future generations. Methods: Using a Participatory Action Research (PAR) approach, researchers and community members collaborated with the director of Olosho Initiatives in study design, participant recruitment, and data gathering. Results: The community identified 31 plant species. Common medicinal usage was determined through In-depth interviews and consensus analysis. From the total, there were 15 plants noted specifically for their preventative health benefits, including body strengthening and immunity enhancement. Conclusions: Almost half of the plants documented had uses that were preventative in nature, which highlights how this traditional knowledge both endures and remains relevant Keywords: Maasai; Ethnobotany; Traditional Medicinal Knowledge